IJCM_107A: A study on healthcare seeking behaviour among the geriatric population residing in southeast Delhi: A community based cross sectional study - Sultana Eram; Roy Sushovan; Alvi Yasir; Gautam Richa (Wolters Kluwer Medknow Publications, 2024)
Background: Health-seeking behaviour is defined as ‘any activity undertaken by individuals who perceive themselves to have a health problem or to be ill for the purpose of finding an appropriate remedy. The severity of the disease among elderly is influenced by one important factor which is health seeking behaviour. To regain their lost health status the elderly must seek the treatment. The way people conceptualize the cause of their health problem and their perception of symptoms plays an important role in seeking healthcare. Health seeking behaviour is influenced by few factors like illiteracy, misconception, income, family composition, social isolation and dependency. Objective: To assess the healthcare seeking behaviour among the geriatric population residing in the field practise area of a Medical College in South East Delhi. Methodology: Community-based cross-sectional study conducted in South East Delhi. • The sample size was calculated as 350 considering a relative error of 3% at 95% level of significance and 10% non-response rate. Stratified random sampling with probability proportional to size was applied to the population registered at UHTC & RHTC area of a medical college in southeast Delhi. Households were selected by systematic random sampling. Persons aged > 60 years from the households were selected for the study. A self-designed, pre-tested, validated, structured questionnaire was used to collect the data. Results In our study it was found that the majority of the participants take treatment when they fall sick ie 99.5%. Of those who take treatment 54% go forconsultation whereas 48% take over the counter medication and 33% do home remedies. Out of the 54% who consult, 78.7% visit Private health facility and 21.3% visit Public health facility. Out of the 78.7% who visit private health facility 65.9% visit Non registered medical practitioner and 7.1% don't even know whether their doctor is registered or not. Majority of the participants ie 86% preferred health facility within 1kms of their house & it was also a major reason for choosing a health facility for consultation. 98% of the participants visit only in case of illness. 52% were accompanied by their children or daughter in law and 26% visited alone. Conclusion: The participants favoured more private than public healthcare institutions. Nearby medical facilities were favoured, and non-registered medical professionals comprised the majority of them. Almost all senior people received therapy of some kind rather than dismissing it as an issue unique to ageing.